Žana - Mičiulytė, Živilė (Lithuania, 2015)
Joan, a 25-year-old acting-school graduate from Lithuania was about to start her career in the Russian Drama Theatre. However, when the war in Ukraine broke, she decided to join the military on the battlefield, where she transports materials for other soldiers.
Verzio Film Festival Submission
Keywords: Documentary films